Crystal structure of 4-(prop-2-ynyloxy)-2,2,6,6-tetramethylpiperidin-1-oxyl - Shailesh K. Goswami; Lyall R. Hanton; C. John McAdam; Stephen C. Moratti; Jim Simpson (Acta Crystallographica Section E, 2014)
The title compound, C12H20NO2, was synthesized from 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (hydroxy-TEMPO) and propargyl bromide. The six-membered ring adopts a flattened chair conformation and carries a propynyloxy substituent in an equatorial orientation at the 4-position. The N—O bond length of the piperidin-1-oxyl unit is 1.289 (3) Å. In the crystal, C—H...O hydrogen bonds combine with unusual C—H...π interactions involving the alkyne unit as acceptor to generate a three-dimensional network.